2004
DOI: 10.1002/lt.20124
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring mycophenolate in liver transplant recipients: Toward a therapeutic range

Abstract: Predose plasma mycophenolic acid (MPA) concentrations measured with a semi-automated enzyme-multiplied immunoassay were related to adverse events (e.g., rejection, leukopenia, infection), drug dose, and clinical status in 147 adult and 63 pediatric liver allograft recipients receiving adjunctive immunosuppression with mycophenolate mofetil (MMF). In 12 of 13 acute rejection episodes, predose MPA levels were below the 1 mg/L cut-off defined using receiver operating characteristic (ROC) curve analysis. The relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 33 publications
(40 reference statements)
2
95
2
2
Order By: Relevance
“…The increase in MPA level and the decrease in cyclosporine with the progression of renal impairment can be the consequence of both the dosage adjustment according to CKD stages and the change in the renal elimination, as MPA is excreted mainly by the kidneys. The individual variations in MPA levels may be connected to the renal and liver function, body mass and genetic polymorphisms in the enzymes and other proteins responsible for drug metabolism and transport (16,17). Since 2008, TDM of MPA is not suggested as a routine test after renal transplantation (8,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in MPA level and the decrease in cyclosporine with the progression of renal impairment can be the consequence of both the dosage adjustment according to CKD stages and the change in the renal elimination, as MPA is excreted mainly by the kidneys. The individual variations in MPA levels may be connected to the renal and liver function, body mass and genetic polymorphisms in the enzymes and other proteins responsible for drug metabolism and transport (16,17). Since 2008, TDM of MPA is not suggested as a routine test after renal transplantation (8,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…ROC curve analysis 14,15) was performed to examine the relationship between adverse events and AUC 0-∞ . ROC curve is a graphical plot of the sensitivity versus 1-specificity for a binary classifier system as its discrimination threshold is varied.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma MPA concentrations within patient groups were not closely correlated with the dose of mycophenolate mofetil but were dependent upon the indication for prescribing MMF, age and serum albumin and creatinine concentrations (Tredger et al, 2004). Tredger et al (Tredger et al, 2004) reported that a therapeutic range of predose MPA plasma levels of 1 to 3.5 mg/L (by immunoassay) is applicable in liver allograft recipients. The potential for MPA toxicity at higher predose plasma levels is in agreement with the findings in renal transplant recipients of Mourad and colleagues (Mourad et al, 2001) who identified at 3 mg/L threshold using ROC curve analysis.…”
Section: Further Studymentioning
confidence: 99%
“…The potential for MPA toxicity at higher predose plasma levels is in agreement with the findings in renal transplant recipients of Mourad and colleagues (Mourad et al, 2001) who identified at 3 mg/L threshold using ROC curve analysis. MMF with the benefit of MPA monitoring, only 6.3% were considered to need 1.5 g twice a day clinically, and 44.7% were prescribed less than 1 g twice a day (Tredger et al, 2004). The drug levels were also influenced by the type of immunosuppressive comedication (Shaw et al, 2002).…”
Section: Further Studymentioning
confidence: 99%